Valores de referência de dois testes de avaliação de capacidade funcional de membros superiores em indivíduos saudáveis - Vanessa Pereira de Lima (2016)
Introduction: Individuals with chronic obstructive pulmonary disease (COPD) often report dyspnea and fatigue while performing activities of daily living (ADLs) involving arms. An upper limb (UL) exercises improves exercise capacity, muscle function and strength of the arms in individuals with COPD and has been increasingly accepted as an important component of pulmonary rehabilitation (PR). As such, there is an increasing interest in the performance evaluation of upper limb, in order to quantify the deficiency and assess the impact of physical training. Among several tests exist to assess functional capacity of the upper limbs, two are highlighted here: unsupported upper limb exercise test (UULEX) and the six-minute pegboard and ring test (6PBRT), denominated as a Portuguese verson in this study as UULEX and TA6 (teste das argolas de 6 minutos) respectively, which can be used to measure the endurance capacity (UULEX) and function of the upper limbs (TA6). Up to the present moment, no study has been published with reference equations for UULEX and TA6 for healthy Brazilian adults. Objectives: To determine reference equation for UULEX and TA6 tests for Brazilian adults, healthy individuals of both sexes; evaluating the relationship between the test results with the age and physical activity level and the repeatability of the tests. Methods: This is a crosssectional study to determine the UULEX and TA6 reference values for healthy Brazilian adults aged over 20 years. The volunteers performed both tests twice each, completed a questionnaire Human Activity Profile (HAP) and were submitted to spirometry. They were recruited from UFMG internal and external community. They completed the questionnaire Human Activity Profile (HAP) and were submitted to spirometry. The volunteers performed both tests twice each, with an interval of 30 minutes between them or until the heart rate and blood pressure returned to baseline. The UULEX is a test that mimics daily activities using upper limbs, limited by symptoms. In this test, the individual had to perform the exercise for as long as possible, participants remained seated in front of a wall mounted panel consisting of eight levels. Participants initially received a plastic bar (PVC) with weight (0.2 kg), and raised both hands in a constant rate of 60 beats per minute (aided by the sound of a metronome), Initially, participants had to move the arms from the pelvic girdle to the first level it should be positioned at the height of the volunteer's knee for 2 minutes as a warmup. From there, every minute, they raised their arms to reach a higher level in the frame. Once the participants have reached its maximum height, the bar 0.2kg was replaced by a heavier (0.5, 1.0, 1.5 until a maximum of 2 kg) or until it reached maximum performance limited by symptoms. For each bar load increase the volunteer should to stay at the highest level for one minute. At the end of the minute, the bar was exchanged for a heavier bar. Scores for dyspnea and arm fatigue were measured (Borg 0-10). TA6 is a test that assesses the functional capacity of the upper limbs and is limited by time. During this test, the volunteers remained seated in front of a table with two upper pins and two lower pins. The frame should be positioned so that the lower pins are at the height of the volunteers shoulders and the two upper pins 20 cm above. Twenty rings are positioned initially at lower pins. Volunteers were asked to move as many rings as possible to the bottom two pins for the top two pins and vice versa with both hands at the same time for six minutes. The number of rings was recorded by a researcher, being recorded every 20 rings moved down or up. Before and immediately after the test, blood pressure (BP), heart rate (HR), perceived exertion and arm fatigue were measured. Results: The sample consisted of 62 individuals (38 female, 24 male), aged 47.87 ± 20.67 years, normal lung function, 67.7% (42) are considered assets and BMI = 25.55 ± 4:48. Equations resulted from the analysis: UULEX (time in minutes) = 15.650 + 1.604 (level of physical activity = sedentary = 0, Active = 1) - 0.109 (BMI) - 0.045 (age). R2 = 0.457 = 1.365 standard estimate error. TA6 (moved rings) = 532296-2735 (old); R2 = 0.409; standard error of the estimate = 69.312. This study showed that UULEX is reproducible in the Bland-Altman analysis, with lower and upper limits of agreement: 2.40 and -2.49 minutes, respectively (bias = -0.05; p = 0.817). Dyspnoea, arm fatigue, heart rate and diastolic and systolic blood pressure increased significantly from pre to post-test in both tests (p = 0.0001). The fatigue pretest arm was higher in the second test, in comparison with the pretest values of the first test (P = 0.0001). Arm fatigue has not increased during the second test (p = 0.417). Conclusion: The results of UULEX and TA6 tests were explained largely by anthropometric attributes, demographic and physical activity of individuals. The equations developed in this study are appropriate to interpret the performance of healthy individuals. Only one UULEX test is needed to perform the measurement of peak unsupported arm exercise in healthy subjects.